Quality Education & Use of Smartphones among School Students: : A case study on selected institutions of Raninagar Upazilla in Naogaon District. (Bangladesh Journal of Public Administration, 2022)
This investigation aims to find the effect of smartphones on the quality of education of School level students as smartphones have become available to them after Covid-19 to ensure e-learning. A mixed method of qualitative & Quantitative analysis was utilised to determine the impact of the smartphone. Random sampling was undertaken among 100 school-level students from four selected schools of Raninagar Upazila in Naogaon District for a questionnaire. An FGD was also made with those schools' teachers to analyse the impact on quality education. This study shows that about 65 percent of high school students got a smartphone after the Covid-19 period. Even though smartphones are beneficial for online classes and preparing study materials, adolescents are becoming reliant on them for unneeded communication. Spending extra time on smartphones hampers their way of achieving quality education. As we cannot ignore the necessity of smartphones in the e-learning process, we can allow smartphones to them but with some restrictions. The use of smartphones can be restricted at night, and morning time can be allocated to get the maximum benefit within a shorter period. Also, keeping a smartphone during class time should be strongly prohibited.